Future matters - CHAN, David (Institutional Knowledge at Singapore Management University, 2017)
I want to share with you my views on some of the issues we face in our social futures, in the context of Singapore. I titled my talk “Future Matters”, and I use the word “matters” in two senses. The first simply refers to the issues about our social futures, that is, what are the matters that we are dealing with. The second sense of the word highlights the point that our social future matters. Most of us will say that it of course matters. But sometimes, our actions do not quite square with the belief that it does, so let us explore why, and how, does it matter. In short, the purpose of my talk is to give you an overview of future matters…